The Severan Buildings of Lepcis Magna An architectural survey - Ward-Perkins, J.B (Society for Libyan Studies, 1993)
The buildings erected in his native city by the Roman emperor Septimius Severus are amongst the most impressive and best-preserved in the Roman world. Because of their unique state of preservation, they give an unparalleled insight into what an architect with an imperial commission could do, when he had the building-materials and technical expertise of the entire empire at his disposal. The buildings excavated by Italian teams between the two World Wars were examined in detail by Ward-Perkins between 1948 and 1953. The study was never completed in his lifetime, though the drawings and much of the text existed at least in draft form. The present publication puts these in the public domain, together with Ward-Perkins' authoritative insights into the process by which such a grand project was executed.